2010
DOI: 10.4103/0976-500x.72348
|View full text |Cite
|
Sign up to set email alerts
|

Role of cinnarizine and nifedipine on anticonvulsant effect of sodium valproate and carbamazepine in maximal electroshock and pentylenetetrazole model of seizures in mice

Abstract: Objective:To study the effect of calcium channel blockers (CCBs) cinnarizine and nifedipine on maximal electroshock (MES)-induced and pentylenetetrazole (PTZ)-induced convulsions and also their effect in combination with conventional antiepileptic drugs (CAED).Materials and Methods:For this study, Swiss albino mice were used. Effects of cinnarizine (30 mg/kg), nifedipine (5 mg/kg), sodium valproate (300 mg/kg) and carbamazepine (8 mg/kg) alone and in combination were studied in MES and PTZ seizure models. Abol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 10 publications
(12 reference statements)
0
4
0
Order By: Relevance
“…We selected VA for this study as it is one of the oldest and most commonly prescribed anticonvulsants in humans (Meunier et al, 1963 ; Pinder et al, 1977 ; Tunnicliff, 1999 ; Who Model List of Essential Medicines, 2013 ; reviewed by Perucca, 2002 ). We applied VA at a dose (300 mg/kg) that doesn't change behavior or EEG activity (Roucard et al, 2010 ) but has protective effect in mice (Brahmane et al, 2010 ; Löscher et al, 2013 ); injected systemically with a single dose of KA (Abdel-Rahmanm et al, 1999 ). We selected the KA seizure induction model as it is one of the most widely used model of seizures that mimics the features and pathophysiology of temporal lobe epilepsy in humans (reviewed by Ben-Ari, 1985 ; Fisher, 1989 ; Vincent and Mulle, 2009 ; Lévesque et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…We selected VA for this study as it is one of the oldest and most commonly prescribed anticonvulsants in humans (Meunier et al, 1963 ; Pinder et al, 1977 ; Tunnicliff, 1999 ; Who Model List of Essential Medicines, 2013 ; reviewed by Perucca, 2002 ). We applied VA at a dose (300 mg/kg) that doesn't change behavior or EEG activity (Roucard et al, 2010 ) but has protective effect in mice (Brahmane et al, 2010 ; Löscher et al, 2013 ); injected systemically with a single dose of KA (Abdel-Rahmanm et al, 1999 ). We selected the KA seizure induction model as it is one of the most widely used model of seizures that mimics the features and pathophysiology of temporal lobe epilepsy in humans (reviewed by Ben-Ari, 1985 ; Fisher, 1989 ; Vincent and Mulle, 2009 ; Lévesque et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“… a Number of animals protected relative to the total number of animals tested. b Number of animals with neurotoxic effects relative to the total number of animals tested. c a ; b ; c ; d ; e ; f ; g ; h d For each test drug, negative control mice received the correspondent vehicle while positive control mice received an anticonvulsant drug with known activity in each seizure model, as described individually for each in vivo assay under Section . …”
Section: Resultsmentioning
confidence: 99%
“…CNZ, along with other members of the calcium channel blockers, has demonstrated anticonvulsant activity in different animal models of seizures including MES, PTZ, and audiogenic induced seizures. However, its anticonvulsant activity in the 6 Hz test had not been previously evaluated. Our studies suggest no activity in this model, at least at the dose tested (30 mg/kg).…”
Section: Resultsmentioning
confidence: 99%
“…Flunarizine, a CCB, was given along with antiepileptic drugs as an add-on therapy and has been found to reduce seizure signicantly, 36 and nifedipine (NFD) was given along with carbamazepine (CBZ) to provide superior seizures control in maximal electroshock (MES)induced and pentylenetetrazole (PTZ)-induced convulsions. 37 There are reports where a patient with classical pattern of bipolar disorder with cycles of mania and depression responds to a combination of CBZ and NFD. 38 In our earlier work 29 we demonstrated that the single and simultaneous solubilization of CBZ and NFD in a single surfactant based micellar media is highly sensitive to the hydrophilic-lipophilic balance (HLB) value and the concentration of surfactants.…”
Section: Introductionmentioning
confidence: 99%